NMR spectroscopic study of some novel N,N-disubstituted phosphonoacetamides - Orelli, Liliana Raquel (2009)
The complete 1H and 13C NMR assignments of a series of tertiary phosphonoacetamides (1) with different N-substitution patterns are reported. N,N-Dialkyl derivatives show two sets of signals due to hindered rotation of the (O)Csingle bondN bond, which originate E/Z diastereoisomers for unsymmetrically N,N-disubstituted derivatives. Complete assignment of the 1H NMR resonances of both rotamers was made on the basis of the magnitude of the diamagnetic shifts (Δδ) experienced by the signals on changing the solvent from CDCl3 to C6D6, and confirmed in the corresponding NOESY spectra. Differential assignment of the 13C NMR signals was performed by HSQC experiments. N-Alkyl-N-phenyl phosphonoacetamides show a unique set of signals corresponding to the E isomers as disclosed by NOESY experiments.